The heterogeneous impacts of energy type and metering systems on household welfare: insights from Ghana and South Africa - Nunoo, Isaac Kwamena (School of Economics, 2025)
This thesis addresses the multifaceted challenges associated with energy delivery and usage in emerging economies, focusing on their impacts on household welfare. It examines the differential effects of electricity and other primary energy sources on household enterprise income in Ghana, highlighting the significant role of energy inputs in enterprise development. Additionally, the study investigates the relationship between prepaid electricity metering and food insecurity in South Africa, revealing how prepayment systems can exacerbate hunger due to their advance payment requirement. Furthermore, the research explores the link between prepaid electricity metering and energy poverty, showing that such systems can increase the likelihood of households becoming energy-poor and resorting to unclean energy sources. Through comprehensive empirical analyses presented in three substantive papers in Chapters Two to Four, this thesis provides critical insights into the policy implications of the Heterogeneous Impacts of Energy Type and Metering Systems on Household Welfare, advocating for targeted government interventions to alleviate food and energy poverty and promote sustainable energy use. Chapter Two presents productive electricity use by non-farm enterprises in Ghana. Energy inputs such as electricity and fuel are essential drivers of enterprise development. The research employs the Ghana Living Standard Survey (GLSS7) data to examine the importance of electricity usage on household enterprise income. This study further shows the relevance of fuel expenditure and other firm characteristics in the enterprise production process. The Lewbel IV method was the main estimation approach used in the study, with the standard Instrumental Variable (IV) results providing a foundational estimation. Both methods showed positive effects of electricity and fuel expenditure on enterprise performance. However, the test for differences between the coefficients of electricity and fuel remained insignificant, highlighting that both energy inputs are equally important. The choice between them should consider other external factors. Furthermore, heterogeneity results based on firm size, type, location, and gender revealed specific differences when considering particular inputs, but these differential impacts were statistically insignificant. Our results have significant policy implications and advance the need for enhanced government electricity programs. Additionally, the government electricity expansion program should be target-specific if the goal is to facilitate household welfare through the productive use of electricity and promote modern fuel supply to improve household enterprise income in Ghana. This chapter's academic contribution includes decomposing the composite energy input in a household enterprise income model into electricity and other primary sources of energy (referred to as fuel) to explore energy's differential and heterogeneous impacts on household enterprise income. Chapter Three discusses food insecurity, a long-time issue in South Africa, with over 12% (7.26 million) of its population suffering from hunger. Food insecurity in South Africa can be attributed to multiple factors, including income, employment, and access to food. However, prepayment systems could also explain food insecurity in the country as they require households to pay in advance, potentially reducing savings. This research investigates the differential impact of electricity prepayment systems and competing policy instruments on food insecurity. Applying robust techniques such as propensity score matching to the General Household Survey 2020 from South Africa, the findings show that households that use prepaid electricity meters have a higher probability of experiencing hunger. Specifically, using prepaid meters increases hunger in families and among adults and children by 3.9%, 4.7%, and 4.4%, respectively. However, hunger marginally decreases when households receive social interventions with prepaid meters. The study further observed multiple burdens of chronic diseases mediating the relationship between using prepaid electricity meters and hunger. Therefore, the policy implications of the results suggest reviewing prepaid metering and subsidy schemes for low-income households. Additionally, the study suggests that providing food assistance programs or subsidies may prove vital in directly addressing hunger in these vulnerable households. This chapter makes a significant academic contribution by pioneering the empirical regression analysis of the heterogeneous relationship between, among other factors, the use of prepaid electricity metering and food insecurity. Chapter Four investigates the relationship between energy poverty and prepayment systems. Energy poverty is a major global issue and has implications for the welfare of individuals and society. The main drivers and barometers in measuring this phenomenon have varied across specific indicators and country-specific case studies. An often underexplained cause is the payment systems constraining electricity consumption in multiple fuel uses, resulting in fuel switching. We use the General Household Survey data of South Africa to explain the impact of prepaid payment systems on energy poverty. Applying fractional probit regression and other robustness methods, the results show that using prepaid meters increases energy poverty between 0.03 and 0.06 percentage points. Using Propensity Score Matching (PSM) to address endogeneity and enable impact analysis through quasi-experimental methods, the study found that households using prepaid meters had a 3.35% higher likelihood of being energy-poor than those using postpaid meters. The study further revealed that households become energy-deprived by switching to unclean energy sources for cooking and heating when given prepaid meters. Specifically, prepaid meters increased biomass for cooking by 5.7%, space heating by 10.9%, and room heating by 4.3%. The results also showed that vulnerable groups or poor South Africans suffer most from energy poverty using prepaid meters. Joint use of prepaid meters and Free Basic Electricity (FBE) could reduce energy poverty. Additionally, the study highlights that the combination of the Reconstruction and Development Programme (RDP) housing scheme with prepaid meters is an effective pro-poor policy in reducing energy poverty. The study's policy implications suggest increased energy subsidies and targeted policy interventions to mitigate energy poverty. This chapter makes a significant academic contribution by pioneering the empirical regression analysis of the heterogeneous relationship between, among other factors, the use of prepaid electricity metering and energy poverty. This study emphasises the imperative for governments to prioritise cleaner energy investments, particularly in electricity, due to its comparable impact on fuel energy but with enhanced environmental sustainability. By highlighting the lack of a significant difference in the effect of electricity and fuel energy, the research underscores the ecological advantages of electricity, urging a shift away from environmentally unfriendly fuel reliance. Additionally, the study makes a novel contribution by extending the known link between payment systems and food insecurity to electricity payment systems, shedding light on an overlooked aspect in the existing literature. Furthermore, it reveals the potential impact of payment systems on food insecurity and advocates for a comprehensive approach that addresses this economic issue for adults and children, considering safeguards not previously explored in policy solutions. The exploration of the role of prepayment technology in explaining energy poverty adds another layer to the study's contributions. Moreover, the emphasis on housing policy and energy subsidies emerges as a significant revelation, serving as a policy guide for Sub-Saharan countries and developing states aiming to enhance household welfare through well-structured policies and clean energy development, aligning with the global campaign against climate change mitigation.